Development of a water air-conditioner for the semi- arid region of Nigeria - Aji, I. S.; Balami, A. A.; Abdulrahim, A. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
The harsh weather condition experienced in Maiduguri between the months of February and June of most years has been a problem to the populace. Buying conventional air-conditioners to ameliorate this problem is difficult for the ordinary people in Maiduguri. In an attempt to lower the temperature of an average 16m2 room, an electrically operated water supply cooling system was designed, constructed and tested and was found to make the room conducive for human comfort. Guard sponge was selected and used out of the existing sponges because it has been found to reduce the ambient temperature better than others. Weather conditions of Maiduguri for the past fifteen years and the unreliability of electricity supply were put into consideration in the design of the water air conditioner. The machine was able to reduce the temperature of an average room (16 m2) by 28% over a period of 42 minutes. The efficiency of the water air-conditioner with respect to the conventional unit is 60%. Seventy five per cent the machine parts were sourced locally, this is to make its production cheap and more affordable to low income earners.